Regulation of ion channel function in human-induced pluripotent stem cell-derived cardiomyocytes by cancer cell secretion through DNA methylation - Zhong, Rujia; Zhang, Feng; Yang, Zhen; Li, Yingrui; Xu, Qiang; Lan, Huan; Lang, Siegfried; Cyganek, Lukas; Burgermeister, Elke; El-Battrawy, Ibrahim; Zhou, Xiao-Bo; Akın, Ibrahim; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background - Cardiac dysfunctions including arrhythmias appear frequently in patients with cancers, which are expected to be caused mainly by cardiotoxic effects of chemotherapy. Experimental studies investigating the effects of cancer cell secretion without chemotherapy on ion channel functions in human cardiomyocytes are still lacking. Methods - The human-induced pluripotent stem cell-derived cardiomyocytes hiPSC-CMs generated from three healthy donors were treated with GI cancer (AGS and SW480 cells) medium for 48 hours. The qPCR, patch-clamp, western blotting, immunostaining, dot blotting, bisulfite sequence and overexpression of the ten-eleven translocation (TET) enzyme were performed for the study. Results - After treated with cancer cell secretion, the maximum depolarization velocity and the action potential amplitude were reduced, the action potential duration prolonged, peak Na+ current and the transient outward current were decreased, late Na+ and the slowly activating delayed rectifier K+ current were increased. Changes of mRNA and protein level of respective channels were detected along with altered DNA methylation level in CpG island in the promoter regions of ion channel genes and increased protein levels of DNA methyltransferases. PI3K inhibitor attenuated and TGF-β mimicked the effects of cancer cell secretion. Conclusions - Gastrointestinal cancer cell secretion could induce ion channel dysfunction, which may contribute to occurrence of arrhythmias in cancer patients. The ion channel dysfunctions could result from DNA methylation of ion channel genes via activation of TGF-β/PI3K signaling. This study may provide new insights into pathogenesis of cardiomyopathy in cancer patients.
Gesehen am 27.09.2022